2022
DOI: 10.21037/atm-21-6868
|View full text |Cite
|
Sign up to set email alerts
|

FNDC5 overexpression promotes the survival rate of bone marrow mesenchymal stem cells after transplantation in a rat cerebral infarction model

Abstract: Background: Most bone marrow mesenchymal stem cell (BMSC) death is caused by the harsh ischemia and hypoxic microenvironment, which impacts the therapeutic effects of transplanted BMSCs. Fibronectin type III domain-containing protein 5 (FNDC5) and its cleaved product, irisin, are reportedly involved in cerebral protective effect. Research into whether FNDC5 plays a key role in the survival rate of BMSCs and cerebral infarction (CI) remains inadequate. The present study aimed to clarify the protective role of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In vitro studies have shown that irisin increases osteoblast and mineralization, and inhibits nuclear factor-kB ligand (RANKL)-induced receptor activation in osteoclasts [ 34 ]. Importantly, FNDC5 / irisin has been found to play a therapeutic role in myocardial infarction [ 35 ] and cerebral infarction [ 17 ] by regulating the function of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that irisin increases osteoblast and mineralization, and inhibits nuclear factor-kB ligand (RANKL)-induced receptor activation in osteoclasts [ 34 ]. Importantly, FNDC5 / irisin has been found to play a therapeutic role in myocardial infarction [ 35 ] and cerebral infarction [ 17 ] by regulating the function of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed mechanism of miR-150-5p on the osteogenic differentiation of BMSCs has not been further studied by Geng Y, et al, but miR-150-5p has been found to inhibit the osteogenic differentiation of ankylosing spondylitis fibroblasts [ 14 ] and adipose-derived stem cells [ 15 ]. At the same time, it is well known that the protein encoded by the FNDC5 gene (iris) has been found to regulate the differentiation of BMSCs [ 16 , 17 ], including promoting the osteogenic differentiation of BMSCs [ 18 ]. Therefore, miR-150-5p may be involved in the regulation of osteogenic differentiation of BMSCs by regulating the expression of FNDC5.…”
Section: Introductionmentioning
confidence: 99%
“…Chizuka Ide et al proved that the beneficial effects of BMSC transplantation on tissue repair, axonal outgrowth, and locomotor improvement in SCI rats 7 9 . However, a significant limitation of BMSCs transplantation in SCI treatment is the low survival rate of transplanted BMSCs at the injury site 10 , 11 . We propose that BMSCs are prone to apoptosis after transplantation, which may be influenced by the presence of myelin debris.…”
Section: Introductionmentioning
confidence: 99%
“…The glycosylated transmembrane precursor protein, Fibronectin type III domain protein 5 (FNDC5), and its extracellular cleavage product of 112 amino acids, named Irisin, have been implicated in numerous processes, including energy metabolism, oxidative stress, anti-aging, and synapse rebuilding [ 19 , 20 ], making it a promising target for modulating autophagy [ 21 ]. Exercise-induced FNDC5/Irisin can protect nucleus pulposus cells against senescence by modulating autophagy [ 22 ] and we have previously shown that overexpression of FNDC5 (OE-FNDC5) can ameliorate autophagy and promote cell proliferation in bone marrow MSCs (BMSCs) upon hypoxia and serum deprivation (H/SD) [ 23 ]. However, the molecular pathways by which FNDC5 modulates BMSCs autophagy are undetermined and the protective effect of FNDC5 after BMSC transplantation for treatment of cerebral infarction needs further elucidation.…”
Section: Introductionmentioning
confidence: 99%